2008
DOI: 10.1002/ajmg.a.32407
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart defects in patients with oculo‐auriculo‐vertebral spectrum (Goldenhar syndrome)

Abstract: The oculo-auriculo-vertebral spectrum (OAVS) is a non-random association of microtia, hemifacial microsomia with mandibular hypoplasia, ocular epibulbar dermoid, and cervical vertebral malformations. Congenital heart defects (CHDs) have been reported in 5-58% of the patients. We analyze the frequency and anatomic features of CHD in a series of 87 patients with OAVS examined between January 1990 and February 2007 with normal chromosomes, ranging in age between 0.1 and 16.8 years. A twin pregnancy occurred in ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
0
13

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 30 publications
9
45
0
13
Order By: Relevance
“…However, we did not find any patients with these cytogenetic abnormalities. Thus, our results were similar to those of Tasse et al 6 and Digilio et al 7 As already described in the literature, we also observed cases of OAVS relating to drug or teratogenic exposure in pregnancy in our sample. These included one patient with gestational exposure to fluoxetine 29 and another to retinoic acid.…”
Section: Discussionsupporting
confidence: 93%
“…However, we did not find any patients with these cytogenetic abnormalities. Thus, our results were similar to those of Tasse et al 6 and Digilio et al 7 As already described in the literature, we also observed cases of OAVS relating to drug or teratogenic exposure in pregnancy in our sample. These included one patient with gestational exposure to fluoxetine 29 and another to retinoic acid.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the reported frequency of cardiovascular alterations ranging from 5% to 58%, [17][18][19][20] this patient had no cardiovascular alterations. Similarly, other systemic abnormalities including pulmonary, genitourinary, and/or gastrointestinal were not present in our patient.…”
Section: -42mentioning
confidence: 70%
“…[7] In the early 1990's, this condition was better understood and it was agreed that, this syndrome may exhibit a wide range of anomalies that includes eye anomalies, [7] disturbance of the central nervous system, cleft lip/cleft palate, [7] facial asymmetry, developmental dental disturbances, [12] skeletal anomalies, [7] mental retardation, [4,11,13] vertebral [14][15][16] and congenital heart anomalies, [17][18][19][20] growth abnormalities, [21] pulmonary abnormalities, [15] and labyrinthine, tracheoesophageal, [15] renal [15,16,22] and genitourinary abnormalities [ Table 1]. [17,20] Its estimated prevalence is 1-9/100,000, [13] with an incidence of 1 in 25,000-45,000 births, [28] with a male to female ratio of 3:2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations